SACRIFICES OF CHILDREN, TEENS AND YOUNG CAMELIDAE DURING LATE INTERMEDIATE IN THE PERIPHERY OF CHAN CHAN, MOCHE VALLEY, NORTH COAST OF PERU - Prieto, Gabriel (2014)
This article presents the preliminary results of recent excavation of a massive sacrificial context at the site of Huanchaquito-Las Llamas, in the northern end of the Moche valley. Results of preliminary field and laboratory analysis of the human and camelid remains are presented, along with a description of their archaeological context. One of the major concerns of this paper is to discuss the nature of the Chimu sacrificial practices, based on the available data for other sites within the Moche valley and in other valleys of the north coast region. From this comparative analysis we develop a working hypothesis for interpreting this sacrifical context. The potential social, political and ideological impact of this kind of sacrificial event is evaluated in the context of the emergence of Chan Chan, the largest urban settlement along the Peruvian north coast prior to the Inca invasion.